Ten Common Structures and Processes of High-Performing Primary Care Practices. Issue 2 (12th March 2022) - Nguyen, Ann M.; Paul, Margaret M.; Shelley, Donna R.; Albert, Stephanie L.; Cohen, Deborah J.; Bonsu, Pam; Wyte-Lake, Tamar; Blecker, Saul; Berry, Carolyn A.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Structures (context of care delivery) and processes (actions aimed at delivery care) are posited to drive patient outcomes. Despite decades of primary care research, there remains a lack of evidence connecting specific structures/processes to patient outcomes to determine which of the numerous recommended structures/processes to prioritize for implementation. The objective of this study was to identify structures/processes most commonly present in high-performing primary care practices for chronic care management and prevention. We conducted key informant interviews with a national sample of 22 high-performing primary care practices. We identified the 10 most commonly present structures/processes in these practices, which largely enable 2 core functions: mobilizing staff to conduct patient outreach and helping practices avoid gaps in care. Given the costs of implementing and maintaining numerous structures/processes, our study provides a starting list for providers to prioritize and for researchers to investigate further for specific effects on patient outcomes.